Comparison of Human Oocyte Activation Between Round-Headed Sperm Injection Followed by Calcium Ionophore Treatment and Normal Sperm Injection in a Patient With Globozoospermia - Niu, Xiangli; Ruan, Qiuyan; Witz, Craig A.; Wang, Weihua (Frontiers in Endocrinology, 2020)
Fertilization failure is common in patients with round-headed sperm, a form of globozoospermia. Artificial oocyte activation is able to assist oocyte fertilization after sperm injection in these patients. Comparisons between oocyte fertilization with or without calcium ionophore have been reported in patients with round-headed sperm. However, no comparison has been reported between round-headed sperm injection followed by calcium ionophone activation and normal sperm injection. In this case report, half of oocytes from a patient were injected with her partner’s round-headed sperm followed by calcium ionophore activation, and the other half of oocytes were injected with a donor sperm without calcium ionophore activation. The injected oocytes were cultured to examine fertilization, embryo development and embryonic aneuploidies in the resulting blastocysts. The fertilization rate was lower in round-headed sperm injected oocytes (3/6) than that in donor sperm injected oocytes (5/6), but rates of blastocyst and aneuploidies were similar in the resulting embryos between the two groups. A euploid blastocyst resulted from round-headed sperm injection was transferred, and a healthy baby was delivered. These results indicate that calcium ionophore treatment can assist oocyte activation in patients with round-headed sperm, but its efficiency to activate oocytes is lower than that induced by a normal sperm injection. However, embryo development and chromosome integrity may not be affected by calcium ionophore treatment.